2022
DOI: 10.1038/s41408-022-00770-x
|View full text |Cite
|
Sign up to set email alerts
|

Venetoclax with decitabine versus decitabine monotherapy in elderly acute myeloid leukemia: a propensity score-matched analysis

Abstract: Venetoclax (VEN) combined with azacitidine (AZA) or decitabine (DEC) has been approved for older adults with acute myeloid leukemia (AML) unfit for intensive chemotherapy based on the pivotal VIALE-A trial. However, this trial only compared AZA + VEN with AZA monotherapy. Therefore, we compared the outcomes of consecutive older adults (65 years or older) with newly diagnosed AML who received DEC (n = 230) or DEC + VEN (n = 74) after propensity score matching to construct a one-to-one matched cohort by the near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…However, although we cannot compare the outcomes between the two different HMA regimens in the current study, substantial data in both the new and R/R settings support the comparable or unsurpassed efficacy of DEC when combined to VEN [14,31,32]. In addition, we also observed promising results with DEC plus VEN in R/R AML setting in our previous study [24,33]. Some case reports have described more successful responses to VEN in EM relapse settings.…”
Section: Discussionsupporting
confidence: 50%
“…However, although we cannot compare the outcomes between the two different HMA regimens in the current study, substantial data in both the new and R/R settings support the comparable or unsurpassed efficacy of DEC when combined to VEN [14,31,32]. In addition, we also observed promising results with DEC plus VEN in R/R AML setting in our previous study [24,33]. Some case reports have described more successful responses to VEN in EM relapse settings.…”
Section: Discussionsupporting
confidence: 50%
“…A direct comparison with the study of DiNardo regarding these characteristics was not possible, as this information was not reported in the publication, or was displayed in a different way (e.g., percentage of patients with anemia instead of average level of hemoglobin). Eleven studies also provided information on the frequency of adverse events during treatment with VEN+HMAs, namely grade 3–4 neutropenia (range among the different studies: 29–93%), thrombocytopenia (range: 14–90%), febrile neutropenia (range 13–80%), tumor lysis syndrome (range: 0–12%) [ 21 , 24 , 26 , 27 , 28 , 29 , 32 , 33 , 35 , 36 , 42 ]. The percentages of patients who discontinued venetoclax because of adverse events ranged in the different studies between 7% and 66% ( Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, although the trial of DiNardo et al reported a median overall survival of 14.7 months (95% CI 11.9-18.7), real-world studies showed substantially lower survival. With the only exception of Cherry et al and Mirgh et al, which reported a median survival of more than 15 months, the other authors showed an overall survival ranging between 4 and 13 months [21,24,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. As a consequence, the pooled median survival in our meta-analysis was 9.37 months (95% CI 8.81-10.5), significantly lower than that reported by DiNardo et al This difference was also confirmed in the secondary analyses that we performed, in particular after we excluded studies enrolling subjects with worse prognoses (i.e., secondary, therapy-related, and TP53mutated AML).…”
Section: Discussionmentioning
confidence: 97%
“…BCL-2 is a key molecule in the regulation of apoptosis of tumor cells and is a novel target for the treatment of leukemia ( 28 ). The BCL-2 protein family is an important regulator of endogenous apoptotic pathways.…”
Section: Discussionmentioning
confidence: 99%